Reginald Pole and the legations of 1537 and 1539 : diplomatic and polemical responses to the break with Rome - Höllger, C (1989)
The thesis deals with the diplomatic career of Reginald Pole at the beginning of his time as a Roman cardinal. Pole's elevation to the cardinalate in 1536 and his quest to persuade Charles V and Francis I to help re-establishing Roman obedience in England are portrayed. Pole's two legations of 1537 and 1539 both failed, it is argued, because of the ongoing hostilities between the houses of Habsburg and Valois: neither the emperor nor the French king could afford to alienate the powerful English ruler, nor were they interested in taking up a costly and risky enterprise on behalf of religion. The differences between the two legations and the different reasons for their failing are discussed. The reaction of the English policy makers both to the legations themselves and to Pole's activities is also considered. The almost complete annihilation of Pole's family in England is linked with Pole's efforts against the English king, and it is shown that the Poles in England lost their lives not because of their alleged treasonable activities in combination with the so-called "Exeter Conspiracy" but because they were used as hostages by Henry VIII against Reginald Pole: it is argued that the "Exeter Conspiracy" is a misnomer, and that the two families involved suffered for reasons of raison d'état and personal revenge. Pole's major writings against the English king in the 1530s, De ecclesiasticae unitatis defensione and the Apologia ad Carlum Quintum, are then examined with regard to Pole's political maxims and his use of anti-Machiavellism in his fight against the English schism. Overall, it is argued in the thesis that Pole was an able politician whose failure is to be explained by the untimeliness of his attempts to unite Charles V and Francis I in a fight for religion and by his own exclusively religious motivation in political affairs.